PERANCANGAN APLIKASI GAME INTERAKTIF ASAH IQ ANAK USIA DINI PADA SEKOLAH TK BERBASIS ANDROID - Devega, Army Trilidia; Veza, Okta; Sitopu, Nirwana (Jurnal Teknik Ibnu Sina (JT-IBSI), 2023)
Human capabilities are increasing along with the pace of technological development, where humans in terms of doing their work mostly use computers. Children aged 4-7 years in the learning process prefer learning while playing, because children at this age prefer colorful, attractive and interactive visual forms. In manual testing, for example by using a piece of paper to test a child's IQ, it is likely that the child will have difficulty and get bored quickly. Advances in Android Smartphone technology are demanding for all parts, not only parents, children are also familiar with this Android technology. For this reason, the authors are interested in conducting research by making an Android-based Children's IQ Test game application that is more interactive by combining multimedia elements that can be controlled via an Android application using a smartphone device. The method for making the IQ Teaser Game Application for Early Childhood is MDLC, consisting of 6 stages, namely: concept, design, material collecting, assembly, testing and distribution. This interactive learning media is made using the Adobe Flash CS6 application. The purpose of this study is that this application can help children aged 4-7 in measuring their IQ abilities more interactively and easily and divert boredom when learning to access their use by utilizing smartphone technology with the Android Operating System. The result or output is an IQ-teaching game application for early childhood at the Ra As Syauqi Kindergarten school which can be installed in the Apk format through the parents of each student.